Italian and Croatian Urban Planning: A Comparative Analysis - Carla D Uva (European Regional Science Association (ERSA), 2006)
Croatian and Italian coasts get involved in seasonal tourism that affects the equilibrium of cities. This phenomenon causes many specific problems that can be solved by suitable urban planning strategies. The actual Croatian coast development seems to replay the situation of the Italian coast 20 years ago: in both cases, the absence of adequate planning causes inability to manage and control urban growth. With respect to these general issues, the author aims at identifyng the planning framework instituted in Italy and in Croatia, through the comparative analysis of local and regional planning instruments such as guidelines, directives and prescriptions for actual and future plans. This study concerns mainly the two coastal areas of Molise, in Italy, and of Split-Dalmacija and Dubrovnik-Neretva counties, in Croatia. The author illustrates how a lack of a suitable physical planning is a serious threat to the development of coastal areas. One of the main causes is that the actual local and regional devices are unable to answer positively to environmental and landscape emergencies, especially in Croatia. Some of the main themes analysed are the following: road and railway systems, architectural, environmental and natural resources, industrial and tourist growth. The planning process has a strategical and leading role in urban governance, both in preliminary and in putting in act phase, in order to reach a sustainable development of the territory. Some interesting results emerge from the comparison of the two government systems and from the resources still available in Italy and in Croatia. These results are useful for continuing the research of development strategies to enhance the territorial value in a compatible way with needs of environmental and nature protection.The planning design guidelines, based on the development capability assessment of the territory, should be answer the requirements of sustainability and valorisation of local resources. This study has been accomplished by the GES.S.TER. Interreg III A Adriatic Cross Border (the Head of this Project is prof. Donatella Cialdea, University of Molise, and the Cross Border Partner is University of Split). The author is a PhD student in "Landscape Analysis and Valorisation" by University of Molise, Italy.
Keywords: 330